19F Magic Angle Spinning Dynamic Nuclear Polarization Enhanced NMR Spectroscopy. (23rd April 2019) - Viger‐Gravel, Jasmine; Avalos, Claudia E.; Kubicki, Dominik J.; Gajan, David; Lelli, Moreno; Ouari, Olivier; Lesage, Anne; Emsley, Lyndon
Abstract: The introduction of high‐frequency, high‐power microwave sources, tailored biradicals, and low‐temperature magic angle spinning (MAS) probes has led to a rapid development of hyperpolarization strategies for solids and frozen solutions, leading to large gains in NMR sensitivity. Here, we introduce a protocol for efficient hyperpolarization of 19 F nuclei in MAS DNP enhanced NMR spectroscopy. We identified trifluoroethanol‐ d 3 as a versatile glassy matrix and show that 12 mm AMUPol (with microcrystalline KBr) provides direct 19 F DNP enhancements of over 100 at 9.4 T. We applied this protocol to obtain DNP‐enhanced 19 F and 19 F– 13 C cross‐polarization (CP) spectra for an active pharmaceutical ingredient and a fluorinated mesostructured hybrid material, using incipient wetness impregnation, with enhancements of approximately 25 and 10 in the bulk solid, respectively. This strategy is a general and straightforward method for obtaining enhanced 19 F MAS spectra from fluorinated materials. Abstract : Immer schneller, immer besser : Eine 19 F‐MAS‐DNP‐verstärkte NMR‐Methode basiert auf der Verwendung einer optimierten Polarisationslösung aus 12 mm AMUPol in Trifluorethanol‐ d 3 (mit mikrokristallinem KBr) und ermöglicht eine 118‐fache 19 F‐Signalverstärkung. Für einen pharmazeutisch aktiven Wirkstoff und fluorierte Materialien wurden exemplarisch 19 F‐ und 19 F‐ 13 C‐CP‐Spektren mit bis zu 600‐facher Zeitersparnis generiert.